The role of adjunctive imaging in chronic total occlusions. (October 2013) - Sapontis, James; Hill, Jonathan
Chronic total occlusion percutaneous intervention is becoming a more common technique with higher success rates. These success rates can be at least partially attributed to the use of classical and contemporary imaging modalities. Preprocedural preparation including patient selection and detailed coronary imaging with the use of computerized tomography are helpful to ensure the highest chance of success. Procedural utilization of intravascular ultrasound and optical coherence tomography are additional tools to help facilitate success during difficult cases. Minimally invasive imaging modalities help determine improvement of left ventricular function or the presence of continued ischemia in the postprocedural period. Newer techniques including high-definition computerized tomography scanners can accurately show details of stent morphology and the presence of in-stent restenosis without the need of a further procedure. Invasive imaging including the use of intravascular ultrasound and optical coherence tomography can highlight the cause of in-stent restenosis and its treatment. Future development and progression of these and other imaging techniques will help the a chronic total occlusion percutaneous intervention operator further improve procedural success and long-term clinical outcome.